Imitation goods in the fashion industry: protection for the consumers / Siti Nur Hajar Hamzah, Farhana Kamarolzaman, and Suhaily Hussain. - Hamzah, Siti Nur Hajar; Kamarolzaman, Farhana; Hussain, Suhaily (2011)
This is a study on imitation goods in the fashion industry and legal protection to the consumer. The main objective of the study is to identify the applicable law in Malaysia that provides protection to consumers who buy imitation fashion goods and analyze their adequacy. The main issue that will be focused is the rights of consumer under the Sale of Goods Act 1957 (SOGA), namely through sale by description and implied condition as to quality or fitness for goods, and the remedies available under the Act. It will also include the comparison between the SOGA in Malaysia, Singapore, and the United Kingdom in terms of sale by description and merchantability of goods in order to identify the weaknesses and limitations in the SOGA 1957. The study also addresses rights for consumer under Consumer Protection Act 1999 (CPA) and the remedies provided under the Act with regard to imitation goods and provides information on Tribunal for Consumer Claims where consumers may claim their rights. This study will also provide a brief comparison between provisions in the SOGA 1957 and the CPA 1999 in terms of the acceptable quality of goods. It will also include relevant suggestions and recommendations to the consumers and the Malaysian government in tackling the problems of imitation goods. As a conclusion, there are still loopholes in the Malaysian sale of goods law regarding imitation goods and the law needs to be added on or amended to make clear provision as to provide protection to the consumers.